ANALISIS PENGARUH BRAND IMAGE, PRICE PERCEPTION, DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAAN PELANGGAN MOTOR LISTRIK DI DKI JAKARTA - Arifianto, Abimanyu Pratama; Suhud, Usep; Krissanya, Nofriska (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Absrtact : This research aims to analyze the influence of brand image, price perception, and perceived value on purchase decision and customer satisfaction for electric motorcycles in Jakarta. The background of this study is based on the increasing air pollution in urban areas, most of which is caused by emissions from fossil-fueled vehicles. Electric motorcycles have emerged as an environmentally friendly and efficient alternative mode of transportation. This study applies a quantitative approach by distributing questionnaires to users of Smoot electric motorcycles in Jakarta. The collected data were analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software to test the relationships among variables. The results indicate that brand image has a positive and significant effect on both purchase decision and customer satisfaction. Price perception is also proven to significantly influence purchase decision and customer satisfaction. Furthermore, perceived value plays an important role in enhancing purchase decisions and customer satisfaction levels. These findings are expected to provide practical insights for electric motorcycle manufacturers to design more effective marketing strategies and serve as a reference for policymakers to accelerate the adoption of environmentally friendly vehicles. This study also contributes to the academic literature on sustainable automotive marketing and consumer behavior. Keywords: brand image, price perception, perceived value, purchase decision, customer satisfaction, electric motorcycle.